Building Energy Efficiency of the Chancellor Complex of Universiti Teknologi PETRONAS - Salehudin Md. Shaarani, Salehudin (Universiti Teknologi Petronas, 2009)
The purpose of this study is to investigate and determine the building energy index (BEI) of the Chancellor Hall in Universiti Teknologi PETRONAS (UTP) and the performance of the envelope to prevent heat gain into the building. This was done by doing an on-site assessment to acquire an actual performance data. The findings from the research were compared to the optimal values set by the Malaysian Ministry of Energy, Water and Communication (MEWC). It was found that the BEI meets the requirement set by the MEWC but the performance of the envelope in preventing heat gain into the building does not meet the requirement. Several ways to improve the building efficiency of the Chancellor Hall are proposed in this research.